Nutrition in the prevention and treatment of sarcopenia in the elderly (Research, Society and Development, 2023)
Sarcopenia is characterized by reduced muscle mass and strength. This is a public health problem that affects the elderly, progressively and significantly affecting their quality and life expectancy. Given the complications associated with sarcopenia, the objective of this integrative review was to characterize the pathophysiology of the disease, as well as identify the nutritional approach aimed at its prevention and treatment. To prepare this integrative review, 34 scientific articles in English and Portuguese were selected through the main databases: Google Scholar and Medical Literature Analysis and Retrievel System Online (Medline). The results demonstrated that the prevention and treatment of sarcopenia are based on an adequate supply of proteins, practicing a Mediterranean diet, supplementation with whey protein, vitamin D, omega 3, leucine, HMB and creatine. Furthermore, it is recommended to practice physical activity in order to promote regular stimulation of muscle tissue.